Development of low power DC-DC converter for thermo-electric generator - Kuthubudeen, Haja Najubudeen (2016)
Thermoelectric module which available commercially is not appealing because of the low power conversion efficiency and looks unattractive. In order to increase efficiency, high efficient low power conversion system is need for thermoelectric modules to achieve it. The power conversion system plays an important role in improving the efficiency of thermoelectric power generation.Thermoelectric generator module characterises enabled as to develop efficient Low Power DC-DC converter. DC-DC converters are used as interface between TEG modules and load.which in turn produce maximum power and optimised by means of MPPT algorithm using microcontroller. SEPIC is a variant type of buck-boost converter that is also able to produce output voltage either higher or lower than its input voltage depending on the switching duty cycle.Removes the problem of unable to have a continuous transfer of energy between the load and the source. Benefits of lower chance of device failure or overheating as well as having low noise operation, enabling higher efficiency conversion. It consists of minimal active components, a simple controller and clamped switching waveforms which can provide low noise operation. If the TEG modules were directly connected to the load, operating point would be set by the load impedance, which would usually result in TEGs not operating at their Maximum Power Point (MPP).Control strategies are developed to control these DC-DC converters, to ensure the modules are always operated at their maximum power point, under conditions of varying temperature and load. MPPT algorithm matches the virtual load seen by the TEG to its actual internal resistance by changing the duty cycle of the converter: Maximum Power Transfer Theorem. For marine engines, exhaust gas temperature is very consistent. So a simple, but effective tracking algorithm was chosen (Perturb and Observe algorithm). When temperature difference is not present, we can possibly provide integrated storage solution. For battery charging application Buck, Boost or Buck-Boost converter can be used. DC-DC converter charges a battery with the help of buck-boost converter.